Data envelopment analysis of the human development index. (11th December 2008) - Lozano, Sebastian; Gutierrez, Ester
The human development index (HDI) measures progress in human development along three dimensions: longevity, knowledge and standard of living. Each dimension is measured by an index and a simple average computed. A total of four indicators are used: life expectancy at birth, adult literacy rate, gross enrolment ratio and gross domestic product (GDP) per capita. In this paper, data envelopment analysis (DEA) is used to combine these four indicators. DEA allows each country to determine the weights of these components thus removing any argument about unfair weights. Consistent with the HDI, the proposed DEA model computes a range-adjusted measure (RAM) of efficiency. Results for the data of years 2000 through 2004 are presented. DEA efficiency scores are shown to be highly correlated with HDI. A sensitivity analysis of DEA efficiency scores w.r.t. the variables has also been performed, showing that the kernel of the index are the literacy and GDP components.